1961
DOI: 10.1029/jz066i004p01225
|View full text |Cite
|
Sign up to set email alerts
|

Erodibility of some California wildland soils related to their metallic cation exchange capacity

Abstract: The inherent erodibility of twenty soils was indexed using Middleton's dispersion ratio and Anderson's surface‐aggregation ratio. These indices were then used as dependent variables for several regression analyses. The milliequivalents per 100 grams of oven‐dried soil for the four most plentiful soil cations (Ca, Mg, K, and Na) were determined and then used as independent variables in the regressions. The best fit to the data was found to be an equation of the type: Both the linear and the curvilinear terms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Anderson (1951) claimed that Middleton's dispersion and erosion ratios are important indices in characterizing the erodability of sediments from 14 Beaseley (1959) concluded that plasticity index and dispersion ratio have pronounced effect on the critical shear stress of cohesive soils in open channels. Wallis and Stevan (1961) defined an erosion index in terms of cation exchange capacity. Krone (1963) related cation exchange capacity with Bingham shear strength.…”
Section: Effect Of Bed Propertiesmentioning
confidence: 99%
“…Anderson (1951) claimed that Middleton's dispersion and erosion ratios are important indices in characterizing the erodability of sediments from 14 Beaseley (1959) concluded that plasticity index and dispersion ratio have pronounced effect on the critical shear stress of cohesive soils in open channels. Wallis and Stevan (1961) defined an erosion index in terms of cation exchange capacity. Krone (1963) related cation exchange capacity with Bingham shear strength.…”
Section: Effect Of Bed Propertiesmentioning
confidence: 99%